Green Management dalam Pembinaan Sumber Daya Pertahanan Negara Sekarang dan Masa Depan - Farah Amalia Fitri; Ananda Vian Saleh Presiden (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2025)
Green Management is a strategic concept emphasizing efficiency, effectiveness, and environmental sustainability through eco-friendly principles. In the context of national defense resource development, applying Green Management is a fundamental urgency. This is because the defense sector involves massive consumption of energy, logistics, and human resources (HR), potentially creating a significant environmental footprint and carbon output. Therefore, Green Management and its core instrument, Green Human Resource Management (GHRM), are essential to establish a new paradigm that balances national security capability with the global mandate for sustainability. The primary objective of this research is to analyze the implementation model of Green Management specifically through GHRM practices in the development of defense HR within institutions like BPSDM Kemhan, identifying challenges and formulating its strategic contributions for the present and the future. This study employs the Systematic Literature Review (SLR) method. The SLR protocol was structured by searching the primary databases Scopus and Web of Science (WoS), targeting  publications  between 2015–2025. Inclusion  criteria  focused  on  empirical  and case  studies relevant to the public/military sector. Following the PRISMA selection process, 24 final studies were included and synthesized using thematic  content  analysis  to measure GM implementation effectiveness. The results indicate that Green Management   can be effectively implemented through three pillars: GHRM (showing the highest implementation rate at 70.8%), green organizational   strategy,   and   continuous   education.   The   key   benefits  of  this  application  are  the  creation  of environmentally conscious defense personnel, significant improvement in operational cost efficiency, reduction of the carbon footprint, and enhancement of institutional image. Implementation alternatives like Green Performance Management and environmental curriculum integration are proposed to address the main constraint found in infrastructure and facilities. Thus, GM and GHRM are crucial not only for internal efficiency but also as a key strategy for developing defense HR that is resilient, professional, and an active contributor to the Sustainable Development Goals (SDGs).